Women, family, and gender in Islamic law - Tucker, Judith E (Cambridge University, 2013)
Examines the position of women in Islamic society, and the ways in which the legal system has shaped the family, property rights, space, and sexuality, from classical and medieval times to the present, with case studies that illustrate discrimination and expectations in the culture.